Feasibility of a real-time pattern-based kinematic feedback system for gait retraining in pediatric cerebral palsy. (May 2021) - Liu, Xuan; Oliveira, Nuno; Ehrenberg, Naphtaly; Cheng, JenFu; Bentley, Katherine; Blochlinger, Sheila; Shoval, Hannah; Barrance, Peter
Introduction: Visual biofeedback of lower extremity kinematics has the potential to enhance retraining of pathological gait patterns. We describe a system that uses wearable inertial measurement units to provide kinematic feedback on error measures generated during periods of gait in which the knee is predominantly extended ('extension period') and flexed ('flexion period'). Methods: We describe the principles of operation of the system, a validation study on the inertial measurement unit derived knee flexion angle on which the system is based, and a feasibility study to assess the ability of a child with cerebral palsy to modify a gait deviation (decreased swing phase knee flexion) in response to the feedback. Results: The validation study demonstrated strong convergent validity with an independent measurement of knee flexion angle. The gait pattern observed during training with the system exhibited increased flexion in the flexion period with maintenance of appropriate extension in the extension period. Conclusions: Inertial measurement units can provide robust feedback during gait training. A child with cerebral palsy was able to interpret the novel two phase visual feedback and respond with rapid gait adaptation in a single training session. With further development, the system has the potential to support clinical retraining of deviated gait patterns.